2019
DOI: 10.5902/2179769232526
|View full text |Cite
|
Sign up to set email alerts
|

Trajetória dos adolescentes usuários de crack até o Centro de Atenção Psicossocial Álcool e Drogas

Abstract: Objetivo: analisar a trajetória percorrida pelos adolescentes usuários de crack até o início do tratamento no Centro de Atenção Psicossocial Álcool e Drogas (CAPS AD). Método: trata-se de um estudo exploratório descritivo com abordagem qualitativa. Participaram usuários, familiares e profissionais atuantes no CAPS AD. Os dados foram coletados por meio de entrevistas semiestruturadas, organizados e tratados pelo software Nvivo 11 e, posteriormente, submetidos a Análise Temática. Resultado: a partir da análise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
0
0
1
Order By: Relevance
“…This information highlights the absence of territorial services in these adolescents' circuits, culminating in their hospitalization. The study by Ribeiro et al (2019b), which aimed to analyze the trajectory of adolescent crack cocaine users until they arrived at CAPSad, corroborates the findings of this research. They identified that the services most frequently used by adolescents present a culture of asylum treatment.…”
Section: It Was My Family… (Ana)supporting
confidence: 80%
“…This information highlights the absence of territorial services in these adolescents' circuits, culminating in their hospitalization. The study by Ribeiro et al (2019b), which aimed to analyze the trajectory of adolescent crack cocaine users until they arrived at CAPSad, corroborates the findings of this research. They identified that the services most frequently used by adolescents present a culture of asylum treatment.…”
Section: It Was My Family… (Ana)supporting
confidence: 80%
“…No CAPS AD, é importante que o profissional de saúde atenda aos usuários de acordo com suas especificidades, para que as estratégias elaboradas sejam mais assertivas na promoção da saúde, prevenção de doenças e prática da redução de danos (24) . Para tanto, o CAPS deve articular ações em conjunto com os serviços presentes em seu território de abrangência, como escolas e a Estratégia de Saúde da Família, incentivando os projetos de vida dos adolescentes (25) .…”
Section: Aspectos éTicosunclassified